'Occupational Health and Safety' - Lamm, F (Pearson Education New Zealand, 2009)
Objectives • To overview theories and principles behind health and safety and accident compensation changes; • To present health and safety and accident compensation legislation; • To identify the shifts between regulatory and self-regulatory approaches; • To indicate the issues being addressed by current public policy debates.